2020
DOI: 10.1371/journal.pone.0229716
|View full text |Cite|
|
Sign up to set email alerts
|

Does a rise in BMI cause an increased risk of diabetes?: Evidence from India

Abstract: BackgroundOvernutrition increases the risk of diabetes. Evidence on the causal impact of overnutrition on diabetes is scarce for India. Considering a representative sample from India, this study examines the causal effect of a rise in the Body Mass Index (BMI) of an individual on the likelihood of being diabetic while addressing the issue of unobserved endogeneity between overnutrition and diabetes. MethodsThe study considers individual level data from Demographic and Health Surveys (DHS) of India, namely, Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…The strong association between BMI and diabetes indicated that even minor BMI changes had adverse effects on the population. A similar study has been reported in the Indian population [9]. A total of 30% of patients had a family history of diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…The strong association between BMI and diabetes indicated that even minor BMI changes had adverse effects on the population. A similar study has been reported in the Indian population [9]. A total of 30% of patients had a family history of diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…Such observations are consistent with prior reports that showed elevated prevalence estimates of prediabetes and undiagnosed T2DM among obese and older individuals. 9,12,14,23,[28][29][30] As for sex differences, our study results showed that HbA1c-defined prediabetes and undiagnosed T2DM prevalence estimates were higher among males compared to females. These results are concomitant with results from the National Health and Nutrition Examination Survey (NHANES) 2011-2014 study, which showed that men are more likely than women to have prediabetes and undiagnosed T2DM.…”
Section: Discussionmentioning
confidence: 64%
“…It was also observed that 80% of COVID-19 patients were overweight/obese. Overweight and obesity are major known risk factors for the development of diabetes and cardiovascular disease [25] . It has become evident that these conditions (diabetes, cardiovascular disease and obesity) make individuals more susceptible to develop severe COVID-19 with increased morbidity and mortality [26] .…”
Section: Discussionmentioning
confidence: 99%